دراسة قياسية لأثر الصادرات على النمو الإقتصادي في الجزائر خلال الفترة 1990 - 2020 - ياسف حسيبة; مجطوح فضيلة (جامعة الوادي university of Eloued, 2024)
هدف هذه الدراسة إلى إختبار العلاقة الموجودة بين الصادرات والنمو الاقتصادي في الجزائر خلال الفترة (1990 – 2020)، تحت إشكالية متمثلة في، ماهو أثر الصادرات على النمو الاقتصادي في الجزائر ؟ تم التطرق إلى المفاهيم الأساسية المعنية بالموضوع ووصفها إحصائيا وكذا صياغة وبناء النموذج القياسي للعلاقة بين متغيرات الدراسة، وذلك بالإعتماد على تقدير العلاقة وفق نموذج الإنحدار الخطي البسيط، كشفت النتائج المتحصل عليها على وجود علاقة طردية قوية بين كل من الصادرات والنمو الاقتصادي في الجزائر خلال فترة الدراسة، وأن الزيادة في الصادرات بقيمة 1 مليون دولار سيزيد النمو الاقتصادي بقيمة 2,391 . Through the study, we are trying to find out the relationship of exports to economic growth from 1990 to 2020. The problem is: What is the impact of exports on economic growth in Algeria? After mentioning the basic concepts related to exports and economic growth and relying on estimating the relationship between the two variables according to a simple linear regression model, the results obtained revealed the existence of a strong direct relationship between both exports and economic growth in Algeria during the study period, and that the increase in exports amounted to $1 million Economic growth will increase by $2,391.
An econometricstudy of the impact of exports on economicgrowth in Algeria during theperiod 1990 - 2020
Keywords: الصادرات; النمو الاقتصادي; التجارة الخارجية; SPSS; الجزائر; exports; economic growth; foreign trade; Algeria